Responding to health policy recommendations on managing opioid use disorder during Russia's invasion of Ukraine: Divergent responses from the frontline to the west - Ivasiy, Roman; Galvez de Leon, Samy J.; Meteliuk, Anna; Fomenko, Tetiana; Pykalo, Iryna; Bromberg, Daniel J.; Madden, Lynn M.; Farnum, Scott O.; Islam, Zahedul; Altice, Frederick L. (Frontiers in Public Health, 2023)
Summary: Russia's invasion of Ukraine on February 24, 2022, followed by Ukraine's Martial law, has disrupted the routine delivery of healthcare services, including opioid agonist treatment (OAT) programs. Directors (chief addiction treatment physicians) of these programs in each region had flexibility with implementing a series of adaptations to their practice to respond to war disruptions like mass internal displacement and legislation updates allowing more flexibility with OAT distribution policies and take-home dosing regulations. We conducted 8 in-depth interviews with directors from seven regions of Ukraine to describe their experiences providing OAT during a specific time during the war and the local crisis-response approach under the emergency policy updates. We categorized their experiences according to the level of exposure to conflict in each region and displacement of patients across the country, which may provide future guidance for OAT provision during the conflict.